Estudio de clima laboral y propuesta de plan de mejora para el área operativa de la empresa TECNOACES CÍA. LTDA. En la ciudad de Quito durante el periodo de Enero – Julio 2015 - Vaca Villarreal, María José (2016)
The study of the work environment today is a transcendental being interfered directly with the organizational environment, this is the main reason why in Tecnoaces could develop this project, linking and working with the operating area key issues topic. Security agents were the direct beneficiaries of this study, together with the Management Company based on the needs identified in a preliminary diagnosis in which the desired factors to assess staff was known, it was possible to obtain important data, which they were the primary justification for lifting information. By designing a measuring instrument, as is the work climate survey, four factors to evaluate as are considered: about the company, on the head, on remuneration, on the conditions and working environment, these parameters they gave a clearer picture about the terms and procedures on which the security personnel served and worked; This measuring instrument was applied to the primary beneficiaries of the project and could gather data that contributed to show what were the factors that would be disrupting the proper work environment in the company and if once gave the necessary guidelines to help you through a plan improvement, all points to improve are treated and considered in order to be presented to the Management of the company and in turn spread to the operating staff.